2017
DOI: 10.5888/pcd14.160043
|View full text |Cite
|
Sign up to set email alerts
|

An Initiative to Facilitate Park Usage, Discovery, and Physical Activity Among Children and Adolescents in Greenville County, South Carolina, 2014

Abstract: IntroductionParks are important settings for increasing population-level physical activity (PA). The objective of this study was to evaluate Park Hop, an incentivized scavenger-hunt–style intervention designed to influence park usage, discovery, park-based PA, and perceptions of parks among children and adolescents in Greenville County, South Carolina.MethodsWe used 2 data collection methods: matched preintervention and postintervention parent-completed surveys and in-park observations during 4 days near the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…One example of person-based interventions included integrating physical activity and nutritional counseling, 40 , 41 which resulted in significant weight reduction, increases in nutritional knowledge, and playing outdoor games to promote physical activity, 42 thereby significantly increasing physical activity and park utilization. Another person-based intervention improved emotional wellbeing (i.e., equilibrium between resources and challenges) 43 and proxy-reported social skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of person-based interventions included integrating physical activity and nutritional counseling, 40 , 41 which resulted in significant weight reduction, increases in nutritional knowledge, and playing outdoor games to promote physical activity, 42 thereby significantly increasing physical activity and park utilization. Another person-based intervention improved emotional wellbeing (i.e., equilibrium between resources and challenges) 43 and proxy-reported social skills.…”
Section: Resultsmentioning
confidence: 99%
“… 31 Relatedly, all but two person-based studies were effective at changing a health-related outcome among children. 31 , 42 Five studies conducted follow-ups after post-tests to assess longer-term intervention effects. 33 - 35 , 37 , 41 Studies using the Fit2Play intervention reported that after 2 years, improvements in cardiovascular health were associated with parks in less segregated areas, indicating a need to examine the social contexts where parks are located.…”
Section: Resultsmentioning
confidence: 99%
“…[ 49 ] 2020 Canada Interventional a) Outcome evaluation b) Process evaluation a) RCT b) Cohort study MA 15.5 Problem behavior prevention b ; Sexual violence and/or adolescent relationship abuse prevention FAIR ET AL. [ 50 ] 2017 USA Interventional a) Outcome evaluation a) Quasi-experimental 0–18 Obesity prevention FLATTUM ET AL. [ 51 ] 2015 USA Interventional a) Outcome evaluation b) Process evaluation a) RCT b) Cohort study 8–12 Obesity prevention; Healthy nutrition promotion GARCIA ET AL.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Parks are a built environment feature considered ideal for PA. They are often in residential neighborhoods, offer several amenities for PA, and available year-round to residents of all ages, at no or low cost [ 14 , 15 , 16 , 17 ]. Given that there are 1,829,533 park acres within the 100 most populous cities in the U.S. and that parks are within walking distance for over 85% of residents of the 10 largest U.S. cities, parks are arguably one of the most important resources available for PA promotion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%